Penggunaan Deiksis dalam Novel Bulan karya Tere Liye: Kajian Pragmatik - Yoni Syahara; Siti Ainim Liusti (Persona: Kajian Bahasa dan Sastra, 2023)
The objectives of this research are: (a) To describe the form of each deixis in the novel Bulan by Tere Liye. (b) To describe the context of the use of each deixis in the novel Bulan by Tere Liye. The type of research used is qualitative research using descriptive method. The results of this study, namely, first, show that the form of each deixis that is mostly found in the novel Bulan by Tere Liye, namely, persona deixis totaling 6,271 data (84.06%) with the form of the aku, -ku, ku-, saya, kami, kita, kamu, -mu, kau, kalian, dia, -nya, ia, beliau, and mereka, followed by social deixis as much as 521 data (6.98%) with the form of the words bapak, ibu, ayah, adik, ibu-ibu tua, tabib, anak, anak, anak muda, mama, papa, tante, tuan rumah, tuan, kapten, miss, and ketua konsil, time deixis as much as 289 data (3.87%) with the form of the tadi, kemarin, lalu, dulu, sekarang, besok, esok, nanti, kelak, besok lusa, nanti-nanti, and besok-besok, discourse deixis 228 data (3.05%) with the form of the word itu, ini, begitu, inilah and begitulah. Place deixis is 151 data (2.02%) with the word form di sini, dari sini, sini, ke sini, di sana, sana, ke sana, and dari sana, out of 7,460 deixis data found. Second, the context of the use of each deixis depends on the speech contained in the novel.